Establishing online communities of practice: the case of a virtual sports coaching community (Introduction) - Whatman, S. (Student Engagement and Educational Rapport, 2016)
This chapter reports upon a pedagogical innovation that aimed to develop a community of practice amongst sports coaches around the world who were completing an online postgraduate course of study. Strategies that reflected diverse understandings of rapport and relational teaching were introduced across 2015. Drawing upon understandings of practice (Kemmis et al., 2014) and conditions or constraints upon practice—practice architectures (Kemmis & Grootenboer, 2008)—the chapter outlines how the sayings, doings and relatings of this community were shaped and shifted by the pedagogical decision-making of the lecturer. Data includes students` assessed contributions to online discussion, peer reviews, anonymous surveys, learning management system analytics and the lecturer`s reflections. Findings show that whilst building a sense of community and rapport in an asynchronous online environment is challenging, it is possible and, indeed, expected.